Integration of Bioengineering and Smart Monitoring for River Flood Control Policy in South Lampung - Lita Istiyanti; Rina Febrina (Journal of Sustainable Civil Engineering (JOSCE), 2026)
Flooding in South Lampung Regency has become increasingly critical due to river sedimentation, land use change, and declining hydraulic capacity. Conventional river normalization approaches tend to focus on structural interventions with limited long-term sustainability. This study aims to analyze the implementation of bioengineering and smart monitoring as an integrated flood control policy approach in South Lampung. The research employed Systematic Literature Review (SLR), Urgency-Seriousness-Growth (USG) analysis, regulatory review, narrative review, and Multi-Criteria Decision Analysis (MCDA). The findings indicate that bioengineering approaches contribute significantly to riverbank stabilization, erosion reduction, and floodplain restoration, while smart monitoring systems improve flood prediction accuracy and operational efficiency through real-time hydrological monitoring. The MCDA results demonstrate that the integration of bioengineering and smart monitoring achieved the highest score in terms of effectiveness, budget efficiency, sustainability, and implementability compared to conventional river normalization approaches. The study concludes that the proposed integrated approach provides a more adaptive, evidence-based, and sustainable strategy for flood control management in South Lampung Regency.